2011
DOI: 10.1002/mnfr.201000640
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and hormonal effects following exposure to mycotoxin deoxynivalenol in the high‐fat diet‐induced obese mouse

Abstract: The effects of ingesting the common foodborne mycotoxin deoxynivalenol (DON) on body weight and composition were characterized in the high fat (HF) diet-induced obese mouse, a model of human obesity. Female B6C3F1 mice were initially fed HF diets containing 45% kcal (HF45) or 60% kcal (HF60) as fat for 94 d to induce obesity. Half of each group was either continued on unamended HF diets or fed HF diets containing 10 mg/kg DON (DON-HF45 or DON-HF60) for another 54 d. Additional control mice were fed a low fat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
(51 reference statements)
3
9
0
Order By: Relevance
“…One factor that may likely contribute to the relative maintenance of metabolic function in pHF mice is the increase in lean mass, which was not observed in aHF mice. These findings are consistent with previous reports, which used NMR to examine body composition in HF-fed mice and reported a pronounced increase in lean mass in pHF compared with LF-or chow-fed controls (34), whereas studies that began HF feeding in adult mice reported little or no change in lean mass (18). Given the primary role of muscle in whole body energy utilization (12), an increase in total lean mass might serve a protective role in maintaining glucose homeostasis to counterbalance the negative impact of fat accumulation.…”
Section: Discussionsupporting
confidence: 94%
“…One factor that may likely contribute to the relative maintenance of metabolic function in pHF mice is the increase in lean mass, which was not observed in aHF mice. These findings are consistent with previous reports, which used NMR to examine body composition in HF-fed mice and reported a pronounced increase in lean mass in pHF compared with LF-or chow-fed controls (34), whereas studies that began HF feeding in adult mice reported little or no change in lean mass (18). Given the primary role of muscle in whole body energy utilization (12), an increase in total lean mass might serve a protective role in maintaining glucose homeostasis to counterbalance the negative impact of fat accumulation.…”
Section: Discussionsupporting
confidence: 94%
“…[27] There is no information about effect of T-2 toxin and HT-2 toxin in combination with leptin on secretion activity of ovarian cells to produce steroid hormones. Kobayashi-Hattori et al [28] observed that DON which is B-trichothecene mycotoxin reduces plasma insulin, leptin, IGF-I, and insulin-like growth factor acid labile subunit as well as increased hypothalamic mRNA level of the orexigenic agouti-related protein.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a noticeable effort was made to describe more precisely the DON-induced anorexia using mice as a model [19,20,21,22,23]. While swine was reported to be the most sensitive species to DON, numerous in vivo and in vitro DON toxicity studies were conducted on rodents and especially on mice which can be considered as a good model for the study of DON toxicity.…”
Section: Don-induced Anorexia In Mice Modelsmentioning
confidence: 99%